Propuesta para el mejoramiento de la productividad en el proceso logístico de aprovisionamiento de una empresa de servicios metalmecánicos (2020)
The research "Design of a proposal for the improvement of productivity in the logistics supply process of the company Metalock de Colombia Ltda. Had the objective of characterizing the current supply logistics process of the company through a critical evaluation of all its operations, identifying opportunities improvement in the Companys current supply logistics process, through the application of a study of times and costs associated with the process and evaluating the operational applicability of the proposed supply model through the generation of alternatives and the application of engineering tolos The final result of this research was an improvement in the times and costs associated with the current logistics process, once the proposal to hire a worker for the warehouse area is addressed, the times of the proposed process were reduced to 17 minutes with 25 seconds per requirement, this in percentages is equivalent to an improvement of 90.61%, likewise, a reduction in the costs of the process of 98.26% was achieved for each technical requirement to the warehouse area that is carried out during the day. It was concluded that an analytical diagnosis of the company's processes allows identifying root causes of its problems, likewise it was achieved that from the hiring of the worker for the warehouse area, the implementation of engineering tools such as: application of methodology of the 5s, costing based on ABC activities, warehouse layout, among others that allow maintaining or achieving efficiency in the activities that facilitate the relationship between the production of goods / services and the flow of materials / products of the company for its normal operation .